An analysis of lowest energy consumption (CPU time) through running several cryptography algorithms with different video formats - Jamil Alsayaydeh, Jamil Abedalrahim; Mohammad Alshannaq, Osama Saleh; Mohammad Nawafleh, Mohammad Mahmoud; Mohammad Nawafleh, Odai Yassin; Baharon, Mohd Rizuan; Baharudin, Zikri Abadi; Zainon, Maslan; Aziz, Azwan (Asian Research Publishing Network (ARPN), 2023)
One persistent obstacle has been verified to be one of the main problems with the main developments in the electronics and technology fields, called: Data Security. The data should be encrypted in order to be quickly and securely linked via the electronic information transfer over the network. The procedure of transforming plain text to ciphered-text is called encryption, where cannot be changed or understood simply by undesirable individuals. It may similarly be described as the science that utilizes mathematics in decryption and encryption data processes. In this article, we consider different significant algorithms utilized for data decryption and encryption in whole areas, for making a comparative study for most vital algorithms. This paper focuses on various current cryptography algorithms types. This paper also analyses the algorithm's security and parameters that define the cryptosystem efficiency.